CORONAVIRUS PANDEMIC IN INDIA AND ITS IMPACT ON HEALTH - Ravikumar, Harita; A. , Jothipriya; K. R. , Don (International Journal of Psychosocial Rehabilitation, 2020)
The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the major pandemic that occurred first in Wuhan, from where it spread to many places all over the globe. The first case in India was reported on January 30, 2020. Due to this pandemic, lockdown has been put forth, which affected the lives of people both in urban and rural areas, where people were not allowed to move freely. The lockdown shattered the economy of the country as well as the globe. Life had become so complicated, and restrictions had a major impact on transport, where public transport stopped functioning. The health of the public was affected the most because they weren’t aware of the precautions at its early stages. People from other places were restricted, the tourism chain was impacted, and most importantly, the education of the children was a big question mark. The financial sector also faced a major impact due to this lockdown. The symptoms are fever, cold, and cough, and it infects the respiratory passage. The treatment has yet to be confirmed; hence, a mixture of antiviral and antifungal drugs is given, and intravenous immunoglobulin treatment has been given. Usage of masks and avoiding being in a crowd are the steps to prevent coronavirus. This article concentrates mainly on the health impacts on people due to coronavirus.